Analisis lembar kerja peserta didik tema 1 kelas v ditinjau dari kelayakan isi, kebahasaan, penyajian, dan kegrafikan di sekolah dasar - Kurniasari, Dian; Poerwanti, Jenny Indrastoeti Siti; Matsuri, Matsuri (Universitas Sebelas Maret, 2021)
This study was conducted to describe the quality of the contents of the Grade V Student Worksheet Theme 1. The quality is decent from the aspect of eligibility requirements, content eligibility aspect, language aspect, presentation aspect, and graphic aspect. This research used descriptive qualitative research methods. Data analysis was done by counting the percentage of the acceptability score of student worksheet. The result showed that the grade V student worksheet Theme 1 has a high level of eligibility in accordance with the standards set by BSNP. This study found that student worksheet still needs some improvement to improve quality of student worksheet. Such as the need to add enough space for student to write something in the student worksheet. But overal the student worksheet has been appropriate with the sepecified indicators. The result showed that aspect of eligibility got score percentage 92,21%, content eligibility aspect got 96,56%, presentation aspect got 99,21%, language aspect got 91,27%, and graphic aspect got 100%. The results of this study indicate that the Student Worksheet used is very feasible and can support learning activities.